Drugs Based on NMDAR Hypofunction Hypothesis in Schizophrenia - Wu, Qiongqiong; Huang, Jing; Wu, Renrong (Frontiers in Neuroscience, 2021)
The treatments for negative symptoms and cognitive dysfunction are the main unsolved problems disturbing psychiatrists around the world. Their mechanisms may be associated with N-methyl-D-aspartate receptor (NMDAR). NMDAR hypofunction hypothesis for schizophrenia was brought up mainly based on the clinical effects of NMDAR antagonists and anti-NMDAR encephalitis pathology. Drugs targeted to augment NMDAR function in brain seemed to be promising in improving negative symptoms and cognitive dysfunction in patients with schizophrenia. In this review, we listed NMDAR-targeted drugs and reported related clinical studies. Then, we summarized their effects especially on negative symptoms and cognitive dysfunction, and we analyzed the unsatisfactory outcomes of clinical studies according to the improved glutamate hypothesis revealed in animal models. We aimed to give perspectives for scientists who sought therapeutic strategies for negative symptoms and cognitive dysfunction in schizophrenia based on NMDAR hypofunction hypothesis.